Rekonstruksi Kurikulum PAI Berbasis Prophetic Intelligence: Respon Teologis-Pedagogis Terhadap Tantangan Etis dan Epistemologis Era Artificial Intelligence - Muhamad Nurul Maulana Rosyada; Sari Hernawati; Nanang Nurcholis (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Technological disruption marked by the massive adoption of Artificial Intelligence (AI) in the global educational landscape presents a paradox for Islamic Religious Education (PAI). On the one hand, AI offers unprecedented efficiency, personalization, and accessibility of learning resources; but on the other hand, it carries existential threats in the form of character degradation, erosion of academic integrity, algorithmic bias, and dehumanization of the educational process. This study aims to formulate a comprehensive framework for reconstructing the Islamic Religious Education (PAI) curriculum by integrating the concept of Prophetic Intelligence as a philosophical, methodological, and axiological foundation. Through a qualitative approach with in-depth library research methods on literature from the 2020-2025 period, this article proposes a reactualization of the four obligatory attributes of the Prophet—Shiddiq, Amanah, Tabligh, and Fathonah—into the structure of a modern curriculum. The study's findings indicate that Prophetic Intelligence is not merely historical material, but an epistemological paradigm that fortifies learners against the phenomena of AI Hallucinations, cognitive dependency, and the loss of digital etiquette. This reconstruction includes a reorientation of educational goals from cognitive knowledge transfer to wisdom formation, the development of ethical digital literacy-based materials, the transformation of learning methods from teacher-centered to hybrid-humanistic, and evaluation that emphasizes authenticity and integrity. This article provides theoretical contributions to the development of Islamic educational philosophy and practical implications for policymakers in designing an educational ecosystem that is adaptive to Society 5.0 while remaining firmly rooted in transcendental values.